Ensino de matemática financeira com utilização de tecnologias - Sousa, Tiago Gadelha de (2014)
The present work is an extremely important issue in the life of every citizen: Financial Mathematics. Chapter 1 is an introduction along with the goals and motivations that led to the realization of this work. Being the main subject and focus of our study, the lack of use in textbooks, technologies as facilitators of learning. In Chapter 2, we talked a little about the history of money and hence Financial Mathematics and also treat the two-funded schemes exist: continuous and discontinuous. Throughout chapter 3, the two types of work arrangements interest: simple and compound, and then describe the types of interest rates. In Chapter 4, we talked about the types of discounts and Chapter 5, we study the equivalence of capital essential to understand, for example, what is the best option (spot or forward). Then, in Chapter 6, we cover the depreciation systems, emphasizing the Constant Amortization System (SAC) and the French system of amortization, also known as the Price Table. Later, in Chapter 7, we analyze some textbooks and concluded that little attention is paid to Financial Mathematics and less still to the use of technologies. This underlies our motivation to propose, along with Chapter 8, a suggested methodology using technologies, namely: simple calculator, scientific calculator and spreadsheet in LibreOffice Calc.